Public Safety Policy in the State of Minas Gerais (2003-2016): Agenda Problems and Path Dependence - Ribeiro, Ludmila Mendonça Lopes; Lopes, Ariane Gontijo (International Journal of Criminology and Sociology, 2018)
In this paper, we reconstitute the Minas Gerais state public safety policy with regard to its agenda and discontinuity over thirteen years (2003-2016). Our purpose is to present reflections that help understand the impasses which ultimately led to the burial of a reputedly successful public policy and to a return to the old way public safety has historically been managed by Brazilian federative states. Our findings inform that the priority agenda of integration promoted by the State Secretariat of Social Defense did manage to institutionalize itself for some time. Nonetheless, as the office goes through political transformations, priorities in the agenda also change, denoting path dependence, given the resumption of the institutional arrangement that existed prior to 2003, with police institutions on one side and the prison system on the other. In this context, the novelty is the permanence of prevention actions.